3 is good
4:
let y = (x+5)^2
interchange x with y
x = (y+5)^2
+-sqrt(x) = y+5
y = -5 +-sqrt(x) or f(x) = -5 +-sqrt(x)
Find the formula for the inverse of each funtion.
3.) f(x)= 2x-5 for this one I have
y= (x+5)/2 is this correct?
4.) g(x)= (x+5)^3
I am stuck on this one.
3 answers
Hi Reiny,
I just have one question for 4.) the problem is g(x)= (x+5)^3
how were you able to convert the equation to the following?
let y = (x+5)^2
interchange x with y
x = (y+5)^2
I just have one question for 4.) the problem is g(x)= (x+5)^3
how were you able to convert the equation to the following?
let y = (x+5)^2
interchange x with y
x = (y+5)^2
my error, did not read the question carefully enough, thought it was squared instead of cubed.
so just change the sqrt to cube root and use only the positive sign.
so last line should be
y = -5 +-cuberoot(x)
so just change the sqrt to cube root and use only the positive sign.
so last line should be
y = -5 +-cuberoot(x)